A gene-specific T2A-GAL4 library for Drosophila - Lee, Pei-Tseng; Zirin, Jonathan; Kanca, Oguz; Lin, Wen-Wen; Schulze, Karen L; Li-Kroeger, David; Tao, Rong; Devereaux, Colby; Hu, Yanhui; Chung, Verena; Fang, Ying; He, Yuchun; et al. (eLife, 2018)
We generated a library of ~1000 Drosophila stocks in which we inserted a construct in the intron of genes allowing expression of GAL4 under control of endogenous promoters while arresting transcription with a polyadenylation signal 3’ of the GAL4. This allows numerous applications. First, ~90% of insertions in essential genes cause a severe loss-of-function phenotype, an effective way to mutagenize genes. Interestingly, 12/14 chromosomes engineered through CRISPR do not carry second-site lethal mutations. Second, 26/36 (70%) of lethal insertions tested are rescued with a single UAS-cDNA construct. Third, loss-of-function phenotypes associated with many GAL4 insertions can be reverted by excision with UAS-flippase. Fourth, GAL4 driven UAS-GFP/RFP reports tissue and cell-type specificity of gene expression with high sensitivity. We report the expression of hundreds of genes not previously reported. Finally, inserted cassettes can be replaced with GFP or any DNA. These stocks comprise a powerful resource for assessing gene function. Determining what role newly discovered genes play in the body is an important part of genetics. This task requires a lot of extra information about each gene, such as the specific cells where the gene is active, or what happens when the gene is deleted. To answer these questions, researchers need tools and methods to manipulate genes within a living organism. The fruit fly Drosophila is useful for such experiments because a toolbox of genetic techniques is already available. Gene editing in fruit flies allows small pieces of genetic information to be removed from or added to anywhere in the animal’s DNA. Another tool, known as GAL4-UAS, is a two-part system used to study gene activity. The GAL4 component is a protein that switches on genes. GAL4 alone does very little in Drosophila cells because it only recognizes a DNA sequence called UAS. However, if a GAL4-producing cell is also engineered to contain a UAS-controlled gene, GAL4 will switch the gene on. Lee et al. used gene editing to insert a small piece of DNA, containing the GAL4 sequence followed by a ‘stop’ signal, into many different fly genes. The insertion made the cells where each gene was normally active produce GAL4, but – thanks to the stop signal – rendered the rest of the original gene non-functional. This effectively deleted the proteins encoded by each gene, giving information about the biological processes they normally control. Lee et al. went on to use their insertion approach to make a Drosophila genetic library. This is a collection of around 1,000 different strains of fly, each carrying the GAL4/stop combination in a single gene. The library allows any gene in the collection to be studied in detail simply by combining the GAL4 with different UAS-controlled genetic tools. For example, introducing a UAS-controlled marker would pinpoint where in the body the original gene was active. Alternatively, adding UAS-controlled human versions of the gene would create humanized flies, which are a valuable tool to study potential disease-causing genes in humans. This Drosophila library is a resource that contributes new experimental tools to fly genetics. Insights gained from flies can also be applied to more complex animals like humans, especially since around 65% of genes are similar across humans and Drosophila. As such, Lee et al. hope that this resource will help other researchers shed new light on the role of many different genes in health and disease.